Long-term Anticoagulant Therapy after Myocardial Infarction in Women. Issue 5618 (7th September 1968) - Borchgrevink, Chr. F.; Bjerkelund, Chr.; Abrahamsen, A. M.; Bay, G.; Borgen, P.; Grande, B.; Helle, I.; Kjörstad, H.; Petersen, A. M.; Rörvik, T.; Thorsen, R.; Ödegaard, A.
Abstract : A multicentre trial from five medical departments in Oslo has been carried out to determine the value in women patients of one year's long-term anticoagulant therapy. Follow-up long-term laboratory control and anticoagulant dosage were performed at one centre (the Rikshospitalet). One hundred and fifty-nine patients were assigned randomly into two similar well-matched groups (control and treatment). Dosage was controlled by Thrombotest, aiming at 10–20% levels, and 50% of the tests were less than 14%. Compared with the control group, the treatment group showed a significant reduction in mortality and in reinfarction rate. No serious bleeding complications occurred. It is concluded that women benefit as much as men from long-term anticoagulant therapy.